Triterpenoids and Steroid from the Leaves of Callistemon citrinus (Curtis.) - Ahmed, Farhana; Rahman, Mohammad Sharifur; Mansur, Muhammad Abdullah Al; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Three triterpenes a one steroidal glucoside were isolated from the methanolic crude extract and its carbon tetrachloride soluble fraction of the leaves of Callistemon citrinus (Curtis.). The structure of the isolated compounds were established as erythrodiol (1), betulinic acid (2), ?-sitosterol-3-O-?-D-glucoside (3) and taraxerol (4) by high field NMR analyses. This is the first report of the occurrence of these compounds in C. citrinus growing in Bangladesh. Dhaka Univ. J. Pharm. Sci. 15(1): 1-5, 2016 (June)